2010
DOI: 10.1017/s0033291710002205
|View full text |Cite
|
Sign up to set email alerts
|

Reality distortion is related to the structure of the salience network in schizophrenia

Abstract: These findings suggest that a deficit of grey matter in the salience network leads to an impaired attribution of salience to stimuli that is associated with delusions and hallucinations in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 47 publications
5
46
2
Order By: Relevance
“…This network deficit is also reported in some patients with autism spectrum disorder [52], which may be consistent with the shared genetic and biological risks between autistic spectrum disorder and some cases of schizophrenia [53]. The pathological role of the insula in abnormal fixation of belief has also been implicated in delusion [54,55].…”
Section: Pathological Roles Of the Insula In Psychiatric And Neurologsupporting
confidence: 73%
“…This network deficit is also reported in some patients with autism spectrum disorder [52], which may be consistent with the shared genetic and biological risks between autistic spectrum disorder and some cases of schizophrenia [53]. The pathological role of the insula in abnormal fixation of belief has also been implicated in delusion [54,55].…”
Section: Pathological Roles Of the Insula In Psychiatric And Neurologsupporting
confidence: 73%
“…In accordance with this, deficits in grey matter volumes in the insula and ACC have also been negatively associated with delusion and hallucinations in psychotic patients. 37 However, grey matter losses in the ACC and insula have been detected across different psychiatric diagnoses and may not be speci c to psychosis. 38 Within the framework of proximal salience, de cient insular detection of external salient events, such as those of rewarding cues, might lead to a faulty allocation of salience to internally generated thoughts and impede the attention to relevant external information.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, most of these investigations evaluated patients with schizophrenia. 26,[31][32][33] The issue of whether morphological changes in the insula were specific to patients with schizophrenia remained a controversial one. 34 However, recent studies have shown a considerable degree of overlap in the regional patterns of brain abnormalities observed across psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…8 Functional and structural neuroimaging studies have found abnormalities in networks which encompass the limbic/paralimbic emotional salience areas and the dorsal neocortical executive control systems to be associated with delusion in both affective disorders and schizophrenia. [8][9][10] However, no studies as yet have evaluated neural morphological abnormalities in patients with BD who experience hallucinations.…”
Section: Introductionmentioning
confidence: 99%